Identification of Fluorinases from Streptomyces sp MA37, Norcardia brasiliensis, and Actinoplanes sp N902‐109 by Genome Mining. Issue 3 (21st January 2014) - Deng, Hai; Ma, Long; Bandaranayaka, Nouchali; Qin, Zhiwei; Mann, Greg; Kyeremeh, Kwaku; Yu, Yi; Shepherd, Thomas; Naismith, James H.; O'Hagan, David
Abstract The fluorinase is an enzyme that catalyses the combination of S‐adenosyl‐L‐methionine (SAM) and a fluoride ion to generate 5′‐fluorodeoxy adenosine (FDA) and L‐methionine through a nucleophilic substitution reaction with a fluoride ion as the nucleophile. It is the only native fluorination enzyme that has been characterised. The fluorinase was isolated in 2002 from Streptomyces cattleya, and, to date, this has been the only source of the fluorinase enzyme. Herein, we report three new fluorinase isolates that have been identified by genome mining. The novel fluorinases from Streptomyces sp. MA37, Nocardia brasiliensis, and an Actinoplanes sp. have high homology (80–87 % identity) to the original S. cattleya enzyme. They all possess a characteristic 21‐residue loop. The three newly identified genes were overexpressed in E. coli and shown to be fluorination enzymes. An X‐ray crystallographic study of the Streptomyces sp. MA37 enzyme demonstrated that it is almost identical in structure to the original fluorinase. Culturing of the Streptomyces sp. MA37 strain demonstrated that it not only also elaborates the fluorometabolites, fluoroacetate and 4‐fluorothreonine, similar to S. cattleya, but this strain also produces a range of unidentified fluorometabolites. These are the first new fluorinases to be reported since the first isolate, over a decade ago, and their identification extends the range of fluorination genes available for fluorination biotechnology.